Safety and efficacy of Holmium-166 selective internal radiotherapy of primary and secondary liver cancer confirmed by real-world data - Schulze-Zachau, Victor; Verset, Gontran; De Bondt, Pieter; De Keukeleire, Katrien; Gühne, Falk; Heuschkel, Martin; Hoffmann, Ralf-Thorsten; Bozzi, Elena; Sciuto, Rosa; Lam, Marnix; Deportós Moreno, Jordi; Debrus, Roxane; et al. (Frontiers in Oncology, 2024)
Holmium-166 has emerged as a promising option for selective internal radiotherapy (SIRT) for hepatic malignancies, but data on routine clinical use are lacking.The purpose of this study was to describe the safety and effectiveness of Holmium-166 SIRT in real-world practice through retrospective analysis of a multicenter registry.Retrospective analysis was conducted on Holmium-166 SIRT procedures performed between July 15, 2019, and July 15, 2021, across seven European centers. Treatment planning, treatment realization and posttreatment follow-up were conducted according to routine local practice. Safety and effectiveness data were extracted from the patients' health records. Primary endpoint analysis was assessed for the entire study population with separate analysis for subgroups with hepatocellular carcinoma, metastatic colorectal cancer and intrahepatic cholangiocarcinoma.A total of 167 SIRT procedures in 146 patients (mean age 66  11 years, 68% male) were retrospectively evaluated. Most common tumor entities were hepatocellular carcinoma (n=55), metastatic colorectal cancer (n=35), intrahepatic cholangiocarcinoma (n=19) and metastatic neuroendocrine tumors (n=10). Nine adverse events grade ≥ 3 according to Common Terminology Criteria for Adverse Events were recorded, including one fatal case of radioembolization-induced liver disease. Response rates and median overall survival for the above mentioned subgroups were comparable to results from previous Holmium-166 trials as well as to results from Yttrium-90 registries.This study confirms that the safety and effectiveness of Holmium-166 SIRT derived from prospective trials also applies in routine clinical practice, reinforcing its potential as a viable treatment option for primary and secondary liver cancer.